Faculty development in low- and middle-income countries – Part I - Shibli, Khalil Ullah; Shibli, Safina (Anaesthesia, pain & intensive care, 2022)
Medicine is a dynamic subject, in the sense that the medical practitioners can never seize to learn; the new discoveries, new therapeutic agents, new diagnostic and interventional procedures and new knowledge continuously evolve with the passage of time. Similarly, teaching and training of new entrants into the specialty and grooming of the existing practitioners is a perpetual task. One of the prime duties of the educators and trainers of today is to prepare educators and trainers for the next generation. In this context, faculty development has gained much importance and is now known to be established in the developed world. However, this concept has not gained its due priority in low and middle income countries due to various reasons. This invited editorial sheds light on this vital issue. Key words: Faculty; Faculty development; Faculty development program; Low and Middle-Income CountriesCitation: Shibli KU, Shibli S. Faculty development in low- and middle-income countries – Part I. Anaesth. pain intensive care 2022;26(2):133-136; DOI: 10.35975/apic.v26i2.1842Invited: January 31, 2022; Received: March 14, 2022, Accepted: March 18, 2022